Measuring Pleasure from Food—Validation of the Food Pleasure Scale by Multiple Techniques and Mixed Methods - Nikoline Bach Hyldelund; Derek Victor Byrne; Wesley Dean; Claudia Squarzon; Barbara Vad Andersen (Foods, 2024)
The development of scales and questionnaires to assess pleasure perception has gained prominence, particularly for evaluating anhedonia in mental disorders. The Food Pleasure Scale is a comprehensive tool exclusively dedicated to measuring pleasure perception from food and food-related experiences. This study aimed to evaluate the face validity and consistency reliability of the Food Pleasure Scale using a mixed methods approach. Twenty-two participants completed the Food Pleasure Scale questionnaire and participated in in-depth interviews to understand their interpretation of the scale items. The interview data underwent thematic analysis, and the quantitative survey data was compared to the qualitative interview responses. Results indicated a high level of understanding of all items in the Food Pleasure Scale, confirming its face validity and applicability. The mixed methods approach supported the consistency reliability, showing consistency between quantitative measures and participants’ explicit and implicit expressions of food pleasure. Furthermore, the study revealed a novel aspect related to food pleasure: the concept of “making an effort”. Overall, this study highlights the comprehensibility, validity, and potential of the Food Pleasure Scale in consumer studies. It effectively captures the subjective experience of pleasure derived from food and food-related encounters, making it a valuable tool for further research in this domain.